AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY - Mulida Zakiyah El Fuadah (Institut Pendidikan Indonesia Garut, 2020)
This study was focused on the analysis of students’ anxiety in speaking English as a foreign language. More specifically, the research sought to find out how the students reduce their anxiety in speaking as foreign language. To achieve the purpose, this study employed a qualitative case study design for investigating and analyzing the natural situation focused on students’ anxiety. To collect the data, this study used semi-structured interview and open-ended questionnaire. Moreover, the participants to be involved in this study are eighteen students in one of boarding schools in Tasikmalaya, Indonesia. The result showed that the students have strategies to reduce their speaking anxiety; first, the students need to prepare the outline and make a concept related to the material, second, avoiding eye-contact to their friends and teacher, third, getting help from peers when students feel anxious about learning, and the last strategy is making the students enjoy in learning English. The findings revealed that those strategies can help the students more less their anxiety in speaking English. Hopefully, this study may portray a clear explanation for readers about students’ anxiety in speaking English and for researchers in investigating relevant area, more importantly, by knowing the students’ responses to their anxiety.